Exosome-derived microRNAs in oral squamous cell carcinomas impact disease prognosis. (September 2021) - Chen, Ching-Mei; Chu, Tian-Huei; Chou, Chih-Chi; Chien, Chih-Yen; Wang, Jian-Shiang; Huang, Chao-Cheng
Highlights: Exosomal miRNA candidates were selected from primary cells and serum of OSCC cases. Oncogenic miR-155/21 suppressed tumor suppressors (PTEN and Bcl-6) in OSCC cells. Tumor suppressor miR-126 inhibited EGFL7 (an oncogene) in OSCC cells. Exosomal miRNAs such as miR-126 in serum may act as biomarkers for OSCC prognosis. Abstract: Objectives: microRNA (miRNA) expression patterns have provided new insight as biomarkers of prognosis as well as novel therapeutic targets for several neoplasms. However, the role of exosomal miRNA in the prognosis of oral squamous cell carcinoma (OSCC) has not yet been completely clarified. Paired primary tumor and normal oral epithelial cells from OSCC patients were obtained, and the exosomal miRNA profiles between them were compared by miRNA microarray analysis. The miRNA levels in the serum exosomes of OSCC patients were verified by real-time quantitative reverse transcription PCR (qRT-PCR) analysis. Finally, the biological functions and the potential as a prognostic marker of the selected miRNA candidates were analyzed in the OSCC cells and patients, respectively. Results: Exosomal miR-155 and miR-21 were significantly upregulated, and exosomal miR-126 was dramatically downregulated in the primary OSCC cells and the serum of OSCC patients. In the analysis of oncogenic behaviors, coculture with either miR-155-rich or miR-21-rich exosomes could promote cell proliferation and invasion accompanied with downregulation of PTEN and Bcl-6 tumor suppressors. Moreover, treatment with miR-126-rich exosomes inhibited oncogenic behaviors and oncogene EGFL7 expression in OSCC cells. Finally, exosomal miR-126 was reduced in the serum of the late-staged OSCC patients, and downregulation of blood exosomal miR-126 was associated with poor survival in OSCC patients. Conclusion: Exosomal miR-155 and miR-21 are oncogenic miRNAs which suppress PTEN and Bcl-6 expression, and exosomal miR-126 acts as a tumor suppressor which downregulates EGFL7 in OSCC. Furthermore, blood exosomal miRNAs may serve as biomarkers for the diagnosis and prognosis of OSCC.